Self-propagating exothermic reaction assisted Cu clip bonding for effective high-power electronics packaging. (November 2022) - Liu, Canyu; Liu, Allan; Jiang, Han; Liang, Shuibao; Zhou, Zhaoxia; Liu, Changqing
Abstract: For the high-power modules packaging, Cu clip bonding has gained growing interest to replace the multiple wire-bonding for the benefits of lower resistance and improved thermal performance, which is especially beneficial for higher reliability. However, the current interconnection materials and bonding processes cannot fully meet the reliability requirements of the emerging Cu clip integrated structure. Brazing alloys can serve in high-temperature conditions, since they have the melting points above 450 °C. However, very limited brazing alloys have been applied in electronics packaging since the processing temperature is also high if needs to be melted. It is promising to develop the low-temperature bonding technology which can serve at high temperatures. In this study, incorporating with the Cu-15Ag-5P brazing alloy as the interconnection material, the self-propagating exothermic reaction (SPER) has been applied to assist the Cu clip bonding process, which provides intense local heating to achieve the interconnects in millisecond scale. The bonding mechanism between Cu-15Ag-5P and Cu substrate is examined and discussed. The research findings promise an effective assembly route viable for the application of high-power electronics packaging. Highlights: Cu clip bonding has been achieved by self-propagating exothermic reaction. Cu-15Ag-5P alloy has been applied as high-temperature packaging material. P in Cu-15Ag-5P acted as flux to break the Cu oxide layer during bonding.